The impact of corporate social responsibility disclosure on corporate reputation: the moderating role of national culture in financial industries of MENA region - Ibrahim O.A. Eriqat; Muhammad Tahir; Abdul Hadi Zulkafli (Cogent Business & Management, 2024)
This study explores the moderating role of national culture on the relationship between Corporate Social Responsibility Disclosure (CSRD) and corporate reputation within financial industries in the MENA region. Utilizing a dataset of 96 financial firms listed in Jordan, Palestine, Qatar, and Kuwait from 2016 to 2020, the study employs the Generalized Method of Moments (GMM) to estimate dynamic corporate reputation models. The findings indicate a positive impact of CSRD on corporate reputation. Notably, individualism as a cultural dimension enhances this positive relationship, whereas generalized trust weakens it. This research contributes to the literature by developing a quantitative corporate reputation index using principal component analysis (PCA), addressing gaps in CSRD research in developing regions, and highlighting the importance of national culture in influencing stakeholder perceptions of CSR activities. The results underscore the need for MENA financial firms to engage in structured CSR initiatives and transparent disclosures aligned with cultural values to enhance corporate reputation. Future research should consider qualitative aspects and expand the scope to other industries and regions.
Keywords: G41; L14; M14; N25; 650; MENA; corporate social responsibility disclosure; corporate reputation; national culture; financial industries